2010
DOI: 10.1097/wnf.0b013e3181cda242
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Effects of Gabapentin for Primary Insomnia

Abstract: Gabapentin enhances slow-wave sleep in patients with primary insomnia. It also improves sleep quality by elevating sleep efficiency and decreasing spontaneous arousal. The results suggest that gabapentin may be beneficial in the treatment of primary insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 39 publications
2
55
2
2
Order By: Relevance
“…36 Gabapentin's positive effects on sleep maintenance were accompanied by less stage 1 sleep and greater slow wave sleep (relative to placebo). This is in agreement with other published reports where the effects of gabapentin on sleep architecture are selective, in that stage 1 is preferentially reduced and slow wave sleep increased, 19,[21][22][23][24][25]27,36 although other findings have been reported (e.g., increase in REM sleep). 24,25 A decrease in light sleep (stage 1) with a parallel increase in deeper sleep (stages 3-4) suggests a deepening or consolidation of sleep, which may play a key role in sleep's restorative processes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…36 Gabapentin's positive effects on sleep maintenance were accompanied by less stage 1 sleep and greater slow wave sleep (relative to placebo). This is in agreement with other published reports where the effects of gabapentin on sleep architecture are selective, in that stage 1 is preferentially reduced and slow wave sleep increased, 19,[21][22][23][24][25]27,36 although other findings have been reported (e.g., increase in REM sleep). 24,25 A decrease in light sleep (stage 1) with a parallel increase in deeper sleep (stages 3-4) suggests a deepening or consolidation of sleep, which may play a key role in sleep's restorative processes.…”
Section: Discussionsupporting
confidence: 93%
“…The beneficial sleep maintenance effects of gabapentin in this study are consistent with findings from another phase advance study that examined gabapentin 250 mg following single and multiple day dosing, 36 and a small open-label trial of gabapentin (mean dose 540 mg/day for 4 weeks) in participants with complaints of difficulty initiating and/or maintaining sleep for at least 3 months. 27 Like the present results, neither of these studies demonstrated an effect on sleep latency.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Insomnia severity of patients across studies was not able to be compared as one study provided scores for the insomnia severity index (39), two for the Athens insomnia scale (41,42) and two for the Pittsburgh sleep quality index (known to measure sleep quality, not insomnia symptoms) (40,43). …”
Section: Demographics and Data Inclusionmentioning
confidence: 99%
“…In addition, gabapentin's positive effects on nighttime awakenings reported in these 3 cases may have been due to its known general sleep-enhancing actions 9 and not to a specific effect on the nighttime awakenings theorized here to have been caused by low serum estradiol and coined LUNAs.…”
Section: Casementioning
confidence: 73%